Fred solved the equation 8(3x - 7) = -6(x + 7) + 4 as shown.

Given 8(3x - 7) = -6(x + 7) + 4

Step 1 24x - 56 = -6x - 42 + 4

Step 2 24x - 56 = -6x + 46

Step 3 30x = 102

Step 4 x = 17/5

Fred made an error between step 1 and step 2.

a.) Explain the error that Fred made.

b.) What is the solution of the original equation?

Given 8(3x - 7) = -6(x + 7) + 4

Step 1 24x - 56 = -6x - 42 + 4

Step 2 24x - 56 = -6x + 46

Step 3 30x = 102

Step 4 x = 17/5

Fred made an error between step 1 and step 2.

a.) Explain the error that Fred made.

b.) What is the solution of the original equation?

8(3x - 7) = -6(x + 7) + 4 Given

24x - 56 = -6x - 42 + 4

24x - 56 = -6x - 38

+6x +56 +6x +56

30x = 18 {added 6x and added 56 to each side}

x = -18/30 {divided each side by 30}

24x - 56 = -6x - 42 + 4

24x - 56 = -6x - 38

**← Fred took -42 + 4 to be 46 instead of the correct -38, shown here**+6x +56 +6x +56

30x = 18 {added 6x and added 56 to each side}

x = -18/30 {divided each side by 30}

**x = -3/5**{reduced}

**- Algebra House**